Integrated Operations (Re-)Scheduling from Mine to Ship - Sampath, Kameshwaran; Tezabwala, Alfiya; Chabrier, Alain; Payne, Julain; Tiozzo, Fabio (Proceedings of the International Conference on Automated Planning and Scheduling, 2013)
Mining companies have complex supply chains that start from the mining location and stretch thousands of kilometers to the end customer in a different country and continent. The logistics of moving the materials from mines to ship is composed of series of optimization problems like berth allocation, ship scheduling, stockyard scheduling, and rail scheduling, which are individually NP-hard. In this paper, we present a scheduling application, called as IBM Optimization: Mine to Ship, for end-to-end integrated operations scheduling. The application is built on IBM ILOG ODM Enterprise with advanced features like rescheduling under deviations and disturbances, and maintenance scheduling. The modeling and computational complexity of integrated scheduling optimization is tamed using hybrid optimization technique that leverages mathematical programming and constraint programming. The application will benefit the mining companies with increased resource usage, higher throughput, reduced cost of operations, and higher revenue.